Frazeologizmy gwarowe w komunikacji internetowej - Kucharzyk, Renata (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2017)
The article discusses the way in which phrasemes of dialectal origin are transferred to the colloquial Polish language. The material basis includes the utterances of the Internet users posted on various kinds of forums and blogs. According to the analysis of the material, folk phraseology is quite expansive and it enriches the colloquial language phraseology to a great extent. Dialectal phrasemes have a specific stylistic value, they carry out assessments, they express the author’s emotions, and sometimes they make a text a bit humorous. Due to such values, they attract the readers’ attention, which is the most important objective in the Internet communication.